Prevalence and outcome of hepatobiliary dysfunction in neonatal septicaemia - Khalil, Sumaira; Shah, Dheeraj; Faridi, M M A; Kumar, Ashwani; Mishra, Kiran (Journal of pediatric gastroenterology and nutrition, 2012)
Cholestatic jaundice and liver enzyme abnormalities have been reported in neonatal septicaemia; the course, pattern, and outcome of such hepatobiliary dysfunction have not been described. One hundred fifty-three neonates with blood culture-positive sepsis were recruited from the neonatal intensive care unit of an urban hospital. Liver function tests were done on day 3 and day 10 in all of the cases. In babies with abnormal results (direct bilirubin >20% of total with a minimum level of 2/dL or alanine aminotransferase [ALT] >50  U/L), tests were repeated weekly for 1 month and then fortnightly for 3 months or until normalization of values. Anthropometry was recorded at all of these visits. Klebsiella pneumoniae was the commonest organism, isolated in 95.4% of subjects. Eighty-three (54.2%) subjects had hepatobiliary dysfunction in the form of either cholestatic jaundice (n = 65 [42.5%]) or derangement in ALT (n = 57 [37.3%]). The onset of cholestasis was seen by day 3 of sepsis in 80% (n = 52), with maximum value of direct bilirubin seen by the 10th day in 90% (n = 58). Only 15% (n = 10) continued to have cholestatic jaundice beyond 30 days of onset of sepsis, and it resolved by 60 days. Hepatic enzyme abnormalities followed a more protracted course: onset by day 10 in 95%, peak value by day 38 in 90%, and normalisation by 60 days in 82% of subjects. The prevalence of any hepatobiliary dysfunction was found less frequently in babies who died as compared with survivors (43.4% vs 56.7%; P < 0.01). The weight, length, and head circumference during follow-up visits were comparable between neonates with or without hepatobiliary dysfunction. Hepatobiliary dysfunction is common in Gram-negative neonatal septicaemia. The onset of abnormalities is early in most cases but ultimately resolve within 2 to 3 months after sepsis. The presence of conjugated hyperbilirubinemia in neonatal sepsis may carry a better prognosis in terms of survival and has no significant effect on growth during early infancy.